The Big 5 and conservation. (30th May 2013) - Caro, Tim; Riggio, Jason
<x xml:space="preserve">Abstract</x> Read the Feature Paper: Understanding heterogeneous preference of tourists for big game species: implications for conservation and management Other Commentaries on this paper: To use tourism as a conservation tool, first study tourists Response from the authors: Conservation marketing and education for less charismatic biodiversity and conservation businesses for sustainable development